Characterization of quenched MD simulated porous carbon electrodes for supercapacitors. (2023) - Khaitan, Ayush; Owhal, Ayush; Nair, Manikantan R.; Sahoo, Soumili; Belgamwar, Sachin U.; Goel, Saurav; Roy, Tribeni
Abstract: Energy storage devices are playing a significant role in reducing the harmful effects of global warming. Automobile manufacturers are already shifting towards electric vehicles (EVs) in order to curb vehicular pollution. One of the significant drawbacks of the current EV batteries lies in their power density which limits their application. Supercapacitors are a category of energy storage devices that keep excellent specific power capacity and can be used in a hybrid setup with Li-ion batteries in order to make EVs with longer life and rapid acceleration. Electrode porosity in supercapacitors performs a major role in defining their energy and power density. This work explores the quenched molecular dynamics (QMD) simulations followed by thorough characterization for understanding the bimodal pore size distribution (combination of micro- & mesopores) of a porous electrode structure for maintaining a high energy and power density. We performed simulations at various quench rates on porous carbon structures ranging from 600 K/ps to 5 K/ps. Once the porous structures obtained room temperature (300 K), we characterized it for its pore sizes that allow ions to move in and out of the pores during charging and discharging, respectively. The interconnected channeling method has been developed to identify the channel throats and their lengths for different cases of quench rates. Direct output of this study will help experimentalists in fabricating tunable porosity in order to achieve high energy density while maintaining a relatively good power density of supercapacitors.